Perceptions on irrigation water supply and utilisation by smallholder agricultural enterprises in Vhembe district of Limpopo Province, South Africa - Nesamvuni, Azwihangwisi E.; Tshikolomo, Khathutshelo A.; Mpandeli, Ndivhudzannyi S.; de Bruyn, Melanie; Hlophe-Ginindza, Samkelisiwe; van Niekerk, Johan (Technium Social Sciences Journal, 2022)
The study investigated perceptions on irrigation water supply and utilisation by Smallholder Agricultural Enterprises (SHAEs) in the Vhembe District of Limpopo Province. More (55.4%) SHAEs depended on surface water as the main source for irrigation. Surface water supply was ranked moderate in the majority of SHAEs, both for summer (58.6%) and winter (69.7%) irrigation and was regarded as always available (51.3%). Groundwater was the main source in 44.2% of SHAEs and was ranked very high for summer (55.7%) and winter (34.4%) irrigation. Groundwater was perceived to have the advantage of being always available in 83.6% of SHAEs while 64.9% complained about higher pumping costs. One in three (33.9%) SHAEs revealed they irrigated two to four times a day while one in five (18.7%) irrigated once every eight to 14 days. The mean amount of water used to irrigate was estimated at 5 300,88l +/- 20 762,91l. Almost two in three (62.6%) SHAEs experienced competition for water. Statistically, signification association was observed between the main source for irrigation and monthly income (X2 (1) = 7.10, p < 0.013) after the Bonferroni adjustment. It was determined that 51,3% of SHAEs with income </= R5000/month used surface water as the main source for irrigation compared to 69.6% with income > R5000/month.